International law and the use of force - Gray, Christine D. (Oxford University Press, 2018)
This book explores the large and controversial subject of the use of force in international law. It examines not only the use of force by states but also the role of the UN in peacekeeping and enforcement action, and the increasing role of regional organizations in the maintenance of international peace and security.